Hello Message Scheme Enhancement in MANET based on Neighbor Mobility - Halim, Berradi; Ahmed, Habbani (Transactions on Engineering and Computing Sciences, 2017)
The key idea behind the routing protocols based in multi hope is to find the required path from the source node to the destination. Since those protocols does not consider the node mobility in their mechanism, we propose enhanced the routing protocols by benefit from localization node and predict the time needed for neighbors to go out of range for a node to increase the robustness of the protocols with the mobility. First, we propose an efficient scheme to predict the neighbor rang out. Second, we designed an enhanced version of OLSR (Optimized Link State Routing) based on the collected data. Third, we conduct an extensive set of simulations to compare the performance of our proposal against OLSR origin.